New stream cipher designs : the eSTREAM finalists - Robshaw, Matthew (Springer, 2017)
The origins of eSTREAM can be traced back to the 2004 RSA Data Secu-rity Conference. There, as part of the, Adi Shamir made some insightful comments on the state of stream ciphers. In particular, with AES [8] deployment being so wide-spread, Shamir wondered whether there re-mained a need for a stream cipher of dedicated design. As arguments against, one might observe that for most applications, the use of the AES in an appropri-ate stream cipher mode [9] frequently offers a perfectly adequate solution. Some also doubt our understanding of how best to design a dedicated stream cipher, a view somewhat supported by the lack of surviving stream ciphers in the NESSIE project [1]. However, as counter-arguments Shamir went on to identify two areas where a dedicated stream cipher might conceivably offer some advantage over block ciphers: (1) where exceptionally high throughput is required in softwareand (2) where exceptionally low resource consumption is required in hardware.